The Moral Economy of the Commons: Ecology and Equity in the Newfoundland Cod Fishery, 1815-1855 - Cadigan, Sean (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1999)
A sense of determinism about the emergence of capitalism and the ruthless over-exploitation of nature in European colonial expansion pervades much of North American environmental and ecological history. The attempts of 19th-century Newfoundland fishing people to regulate access to common-property marine resources suggests that some European settlers were also capable of non-capitalist forms of ecological management. Fishers protested against the introduction of new fishing technology in response to localized exhaustion of cod stocks. Some of these protests involved the destruction of newer equipment, while others were anonymous assaults on the equipment's owners. The protests represented attempts to forestall the depletion of marine resources by the further capitalization of the fishery. By the late 1840s the demands for conservation measures became more organized politically under the leadership of mercantile agent Willam Kelson. Although he was conservative and paternalistic, Kelson's criticism of the unrestrained employment of technology in the fishing industry had radical implications. Kelson supported the desire to preserve a customary and equitable right of access to fish for present and future generations. The preservation of equitable access may been seen as an ecological norm of a moral economy that ran counter to the individualistic and accumulative values of a nascent local capitalist political economy.